PENGARUH PERSEPSI HARGA, SUASANA CAFE DAN SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN CAFE G.COFFE TAHUN 2023 (STUDI KASUS PELANGGAN CAFE G.COFFE KOTO BARU) - Suci Rahmadani (MANAJEMEN DEWANTARA, 2024)
Nowadays, business development in the competitive industry is very tight because each entrepreneur in indonesia is very careful and creative in developing competitive strategies. The aim is for entrepreneuurs to compete to provide the best that suits their customers’ needs, especially in culinary food and coffe. Recently ,culinary food and coffe have become a trend for all groups, especially among young people or the millenial generation. Technological factors are one of the factors tht support the development of food and coffe culinary trends because the millenial generation likes to share their activities on social media, including gathering or hanging out at cafes and coffe. In the cafe business, g.coffe can make the cafe look more attractive, so the coffe products or types of food offered must have diferent tastes, menu variants and atmosphere. The results of this research state that there is a relationship between perceptions of cafe atmosphere and customer loyalty. The cafe atmosphere itself is one of the elements that companies use to atract consumers to thair retail stores. Frrom the explanation is concluded that quality is the totality of the characteristic features of a product or service that has the ability to satisfy needs. Defining service quality as a measure of how well the level of service provided is able to meet customer expectations, so if we conclude the definition of service quality, customer satisfaction can be formed. And finally, if customer satisfaction occurs repeatedly,customer loyalty will be formed. Proper service implementation will be able to satisfy consumers. Customer satisfaction will occur when the expected service is in accordance with the service received (perceived service).